2012
DOI: 10.3945/an.111.001131
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Universal Provision of Iron through Home Fortification of Complementary Foods in Malaria-Endemic Areas

Abstract: Home fortification of complementary foods with iron and other micronutrients is a low-cost strategy for filling nutrient gaps in the diets of infants and young children, but there has been uncertainty about the safety of universal provision of iron via home fortification in malaria-endemic areas. Based on the current understanding of the potential mechanisms of adverse effects of iron, the risk can probably be minimized by using the lowest possible efficacious dose of iron, preferably delivered in small amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Such an outcome could be mediated for instance by displacement of breast milk or nutritious complementary foods from the childÕs diet, an increase of malaria or other infectious disease morbidity because of the iron content of the supplement, or a change in the recipientsÕ intestinal microbiota (22)(23)(24). Earlier studies in Malawi have, however, suggested that LNS provision does not decrease breast milk or complementary food intake (25)(26)(27), and no indication was found of a slower postnatal growth velocity among children were received LNSs than children who did not receive supplements (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Such an outcome could be mediated for instance by displacement of breast milk or nutritious complementary foods from the childÕs diet, an increase of malaria or other infectious disease morbidity because of the iron content of the supplement, or a change in the recipientsÕ intestinal microbiota (22)(23)(24). Earlier studies in Malawi have, however, suggested that LNS provision does not decrease breast milk or complementary food intake (25)(26)(27), and no indication was found of a slower postnatal growth velocity among children were received LNSs than children who did not receive supplements (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…This might lead to a transient peak of nontransferrin-bound iron (NTBI), a possibility discussed in some detail by Dewey and Baldiviez (7) in the accompanying paper. NTBI could lead to oxidant damage and/or ready availability of iron to plasmodial parasites and/or provision of substrate for iron-seeking bacteria.…”
Section: Basic Sciencementioning
confidence: 99%
“…This has led to a policy vacuum at both the global and country levels because the proposed targeted approach is very difficult to implement and implies treatment of iron deficiency (ID) as opposed to prevention, thus putting millions of children at risk of the silent sequelae of ID. This was the background to the current symposium “Tackling Iron Deficiency and Anemia in Infants and Young Children in Malaria-Endemic Areas: Moving From Controversy Toward Guidance for Safe, Effective, and Feasible Policies and Programs” summarized in the accompanying papers (47). The purpose of this paper is to identify the residual research needs and make recommendations as to their prioritization given the urgency with which we need to surmount the policy stasis imposed by the Pemba results.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, and perhaps more importantly, this atmosphere of fear and uncertainty also hampered the discussion and introduction of new programs that provide iron to infants and young children in forms other than the traditional iron supplements. There has been a paradigm shift, most notable since the Pemba trial, from approaches that deliver only 1 or 2 micronutrients (e.g., iron or iron/folic acid supplementation) to those that aim at improving infant and young child nutrition more broadly (6, 7). A major focus of the latter approach is improving the quality of complementary foods, including increasing the density of iron and other micronutrients, most commonly through home fortification using multiple micronutrient powders or lipid-based nutrient supplements.…”
mentioning
confidence: 99%
“…This paper also reviews the screening technology available and under development and reports on results from field testing noninvasive devices to measure hemoglobin levels. This is followed by a review of the evidence on safety of universal provision of iron in malaria-endemic areas through home-fortification products, which also includes an overview of the current theories on the biological mechanisms responsible for the adverse effects of iron on infectious disease (6). The fourth paper is an overview of the important research needs from basic science to global policy (27).…”
mentioning
confidence: 99%